HPLC-DAD-APCI/ESI-MSn analysis of carotenoids and α-tocopherol in Costa Rican Acrocomia aculeata fruits of varying maturity stages - Schex, Roland (2018)
Carotenoids and tocopherols were characterised in the meso- and exocarp of wild-growing Costa Rican Acrocomia aculeata fruits. Comprehensive profiling of these lipophilic micronutrients in fruits of three varying maturity stages was conducted for the first time. A method for the simultaneous extraction and quantitation of carotenoids and α-tocopherol was developed and validated. Detailed HPLC-DAD-APCI/ESI-MSn analyses enabled the identification of α-tocopherol and 25 carotenoids. The latter comprised antheraxanthin, β-carotene, lutein, luteoxanthin, neoxanthin, phytoene, phytofluene, violaxanthin, zeaxanthin, and several (Z)-isomers of the aforementioned compounds. Quantitation by HPLC-DAD/FLD revealed total carotenoid concentrations of 872 ± 178 and 3075 ± 407 μg/100 g fresh weight in the meso- and exocarp of fully ripe fruits, respectively. In both fruit fractions, progressing maturation resulted in the accumulation of phytoene, phytofluene, (all-E)-zeaxanthin, (all-E)-antheraxanthin, and (all-E)-violaxanthin. Carotenoid profiling was supported by multivariate data analysis. Carotenoid precursors and xanthophyll cycle pigments characterised Macauba fruits of full maturity.